2015
DOI: 10.1177/000313481508100918
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Ultrasound and Pathologic Status of Axillary Lymph Nodes in Clinically Node-negative Breast Cancer Patients

Abstract: Sentinel lymph node biopsy (SLNB) is the standard of care for axillary staging in clinically node-negative breast cancer patients. Ultrasound (US) has shown promise when used to assess axillary lymph nodes preoperatively, thus aiding surgical decision making. We examined the correlation between preoperative US and SLNB results to further clarify the role of US in clinicopathologic staging of breast cancer when the axilla is clinically negative on physical examination. Our institutional cancer registry was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Some studies showed that these techniques, especially if combined, had good levels of sensitivity, specificity, and accuracy, although not comparable to biopsy. Some other works, even recently, reported different results overall for the sensitivity. We tried to evaluate the impact of the use of contrast‐enhanced sonography in this general context.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies showed that these techniques, especially if combined, had good levels of sensitivity, specificity, and accuracy, although not comparable to biopsy. Some other works, even recently, reported different results overall for the sensitivity. We tried to evaluate the impact of the use of contrast‐enhanced sonography in this general context.…”
Section: Discussionmentioning
confidence: 89%
“…As palpation is inaccurate (29), AUS is performed to provide more relevant information. AUS alone has a reported sensitivity of 39-60%, specificity of 90-96%, PPV of 80-91%, and NPV of 75-83% (6,30,31). This implied that despite of an acceptable specificity above 90%, prior to surgery about 40-60% of nodal metastases cannot be found by AUS and about 20-25% of patients with a negative AUS have been assessed as modal metastases after surgery.…”
Section: P-values Were Calculated By Using χ 2 Test or Wilcoxon Rank-mentioning
confidence: 99%
“…While SLNB remains the gold standard for the assessment of axillary nodal burden [3], it may be an unnecessary procedure in the HNB group who require an ALND if we can identify this subgroup preoperatively [4]. However, only a limited amount of data is available to distinguish the HNB group preoperatively.…”
Section: Introductionmentioning
confidence: 99%